2015
DOI: 10.1152/advan.00116.2014
|View full text |Cite
|
Sign up to set email alerts
|

A puzzle used to teach the cardiac cycle

Abstract: The aim of the present article is to describe a puzzle developed for use in teaching cardiac physiology classes. The puzzle presents figures of phases of the cardiac cycle and a table with five columns: phases of cardiac cycle, atrial state, ventricular state, state of atrioventricular valves, and pulmonary and aortic valves. Chips are provided for use to complete the table. Students are requested to discuss which is the correct sequence of figures indicating the phases of cardiac cycle. Afterward, they should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 22 publications
4
65
0
6
Order By: Relevance
“…5,6 Using recreational games during classroom lecture decreases stress among students and thereby provides a relaxed environment to learn better. 1,13 In many of the previous studies, crossword puzzles were found to contribute to the overall learning of the undergraduate medical students. [5][6][7][8][9][10] Crossman EK in his study on psychology course also showed that students achieve better scores after using crossword puzzles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Using recreational games during classroom lecture decreases stress among students and thereby provides a relaxed environment to learn better. 1,13 In many of the previous studies, crossword puzzles were found to contribute to the overall learning of the undergraduate medical students. [5][6][7][8][9][10] Crossman EK in his study on psychology course also showed that students achieve better scores after using crossword puzzles.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Crossman EK in his study on psychology course also showed that students achieve better scores after using crossword puzzles. 13 A contributing factor to the enhanced learning skills in crossword puzzles is due to dry and monotonous nature of the regular didactic lectures. Studies have shown that adult students have an attention span of 20-30 minutes and hence it is good to shorten the traditional lecture and implement recreational learning exercises such as crossword puzzles, online quizzes, and audio-video clips.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, in groups of 4-5 participants, students received the puzzle containing pictures of the cardiac cycle phases, one table and chips for filling the table as described previously (see Marcondes et al, 2015). They were asked to identify the correct sequence of the figures of the phases of the cardiac cycle.…”
Section: Activity With Cardiac Cycle Puzzlementioning
confidence: 99%
“…Considering the teaching of the cardiac cycle, it has been developed by our group a cardiac cycle puzzle (Marcondes et al, 2015). Students of Biology, Medicine, Pharmacy and Nursing careers evaluated the cardiac cycle puzzle as useful for their learning (Marcondes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation